Navigating at the margins: family, mobility and livelihoods amongst Rohingya refugees in Bangladesh - Olney, Jessica; Mercy, Rezaun Nahid; Ahamed, Kawsher; Badiuzzaman, Muhammad (Brac University and The Asia Foundation, 2022)
Includes bibliographical references (pages 43- 44).